Development and implementation of synthetic cast iron casting technology for the manufacture of a friction wedge (Международный научный журнал «Инженер», 2026)
The article presents a step-by-step technological process for manufacturing a friction wedge for freight cars,designed to damp vibrations, using synthetic cast iron casting. Special attention is given to the preparation ofmolding and core mixtures, the formation of a disposable sand mold from compacted sand, and the preparationof charge materials. The study examines experimental results of synthetic cast iron production using variousproportions of steel scrap in an induction crucible furnace. Methods for chemical composition control,assimilation coefficients of alloying elements, energy consumption indicators, and hardness data based on meltcertificates are analyzed. An improved method for melting synthetic cast iron using steel scrap and ferroalloysfor carburization and alloying is proposed, along with a detailed scheme for producing the friction wedge in adisposable sand mold. The development and implementation of this technology are especially relevant underconditions of limited access to high-quality cast iron scrap and the need to reduce production costs. The use ofsingle-use sand molds, along with the careful selection and control of molding mixtures, ensures consistentcasting quality and compliance with current standards.